Volatile composition and nutritional quality of the edible mushroom Polyporus tenuiculus grown on different agro‐industrial waste - Omarini, Alejandra Beatriz (2010)
The volatile composition and the nutritional value of Polyporus tenuiculus grown on supplemented and nonsupplemented wheat straw and willow sawdust were determined. Thirty-nine volatile compounds were detected, including acids, esters, alcohols, hydrocarbons, aldehydes and ketones. The main volatile compound in all samples was 1-octen-3-ol, with increasing levels in mushrooms cropped on supplemented substrate. In addition, several precursors of this alcohol were identified in lower percentages. Mushrooms grown on supplemented substrates showed lower fat (5.2–5.7%) and carbohydrate contents (48.2%) and higher protein content (22–22.5%). Fibre and ash contents showed some variations between types of substrates. Compared to other edible fungi, P. tenuiculus high fibre and protein contents point to this species as a healthy nutritional alternative of interest for the food industry. Moreover, the wide spectrum of volatile compounds of P. tenuiculus reveals great potential for biotechnological applications such as the production of ‘‘non artificial’’ mushroom flavour.